Food review app with chatbot - Wu, Zhao Yi (Nanyang Technological University, 2024)
Food related online platforms have been very prevalent over the last decade as people like to use them to decide on what they should try eating next. Online platforms include food review forums and food delivery applications where they both allow users to post ratings, photos and detailed descriptions of restaurants or dishes they have tried.